Safety and efficacy of testosterone gel in the treatment of male hypogonadism - Kishore M Lakshman (Dove Medical Press, 2009)
Kishore M Lakshman, Shehzad BasariaSection of Endocrinology, Diabetes, and Nutrition. Boston University School of Medicine, Boston Medical Center, Boston, MA, USAAbstract: Transdermal testosterone gels were first introduced in the US in 2000. Since then, they have emerged as a favorable mode of testosterone substitution. Serum testosterone levels reach a steady-state in the first 24 hours of application and remain in the normal range for the duration of the application. This pharmacokinetic profile is comparable to that of testosterone patch but superior to injectable testosterone esters that are associated with peaks and troughs with each dose. Testosterone gels are as efficacious as patches and injectable forms in their effects on sexual function and mood. Anticipated increases in prostate-specific antigen with testosterone therapy are not significantly different with testosterone gels, and the risk of polycythemia is lower than injectable modalities. Application site reactions, a major drawback of testosterone patches, occur less frequently with testosterone gels. However, inter-personal transfer is a concern if appropriate precautions are not taken. Superior tolerability and dose flexibility make testosterone gel highly desirable over other modalities of testosterone replacement. Androgel and Testim, the two currently available testosterone gel products in the US, have certain brandspecific properties that clinicians may consider prior to prescribing.Keywords: testosterone gel, Androgel, Testim, hypogonadism